Improving swimming stroke using reverse teaching: a case study - Sherman, C. A.; Rushall, B. S. (Applied research in coaching and athletics annual 1993, 1993)
The purpose of the present study was to plan and implement a reverse progression teaching strategy for the repetitive skill of front crawl swimming. This application was intended to describe in detail the procedures, treatments, and results involved in modifying an already successful swimmer's hand and arm technique.